Experiences of service users involved in recruitment for nursing courses: A phenomenological research study. (November 2017) - Stevens, Katie; Bernal, Cathy; Devis, Kate; Southgate, Andrew
Abstract: The aim of this study was to gain insight into service users' experiences of participating in recruitment for Adult, Mental Health and Child nursing studies at the authors' university; to establish potential motivations behind such participation; and to make suggestions for improved future practice. The involvement of service users in nurse education and recruitment has for some years been required by the Nursing and Midwifery Council, but there is a dearth of publications on the meaning of that involvement to participating service users. It is hoped that this study will contribute to this body of knowledge. A phenomenological approach was selected, field-specific focus groups of service users being facilitated using a semi-structured interview format; these were audio recorded and transcribed. The data was analysed using thematic analysis. Participation was subject to the service users having been involved in recruitment to nursing studies at the authors' university and the focus groups took place either at the university or at the child participants' school. Themes identified demonstrated largely positive experiences and a sense of meaningful involvement for all concerned. Findings indicated a close link between the values of the participants and those of the wider NHS, benefits to a sense of wellbeing and achievement, as well as the need for greater ownership of the recruitment process by service users. Potential lessons for academics wishing to promote greater service user involvement in student recruitment are articulated. Highlights: Service user involvement in recruitment to nursing is valuable and necessary. Further control by service users for the process of recruiting nurses is suggested. Partnership working in planning and delivery of recruitment is vital to success. Service users values reflect those of the wider NHS constitution. Service users offer insight into desirable characteristics of nursing candidates.